هندسيات تشكيل العمارة الداخلية للمسكن الإسلامي وارتباطها بالمعايير الوظيفية البيئية - إمام، محمد حسن; إبراهيم، أحمد محمد محمد; إبراهيم، نسمة سيد جلال (الجمعية العربية للحضارة والفنون الإسلامية, 2024)
تُعد أسس هندسيات تشكيل العمارة الداخلية الإسلامية للمسكن أحد أهم المحددات الوظيفية البيئية التي هي مجالاً للدراسة في العديد من الأبحاث العلمية؛ فمن خلالها نستطيع معالجة العديد من المشكلات لمعايشة وراحة الإنسان داخل مسكنه، فهندسيات التشكيل تمكن المصمم من الأدوات التصميمية التي تحقق الهدف الوظيفي البيئي للفراغ عن طريق محددات تصميمية تحقق التوازن السيكولوجي والفسيولوجي للإنسان في محيط بيئته معتمدة علي كافة العناصر الطبيعية المحيطة في تشكيل المبني دون استخدام أي مؤثرات صناعية، ومنها تم صياغة كافة عناصر التصميم الداخلي من تشكيل فناء المسكن وفراغاته فهو منفتح للداخل ويتم توجيهه مع تناسب طوله وعرضه (مربع أو مستطيل) مع ارتفاعه بنسب محدده تصميمياً لخدمة الوظيفة المرجوة، ويظهر بروز بعض النوافذ كذلك المطلة علي الفناء أو الشارع أو الحديقة الخلفية بما يخدم الوظيفة والهدف من التصميم، وقد تأثرت المفردات المعمارية للمنشآت السكنية كذلك بالتشكيل الهندسي فنجد المشربيات، الشخشيخة، الملقف والعقود والتي تتناسب مع نسب تشكيل الفراغ، ومن هنا يتجلى بكل مرحلة أثر هندسيات التشكيل، فإن التشكيل الهندسي عبر عن المستوي الإبداعي للمصمم في ضوء محددات تصميمية وظيفية بيئية لا تتغير؛ فإن تحليل أسلوب التشكيل للمسكن بالعصر الإسلامي ومفرداته يُمكن المصمم من فهم وإدراك آلية التعامل مع الأدوات التشكيلية الهندسية التي من خلالها يستطيع تطويع الفراغ للاستجابة للمحددات الوظيفية البيئية Geometrical forming basics for designing residential Islamic interior spaces are deemed one of the most important environmental functional parameters that is a field of study in many kinds of research, the environmental functional parameters help us to solve existing problems to attain human comfort inside the house. The Geometrical forming provides the designer with the tools that he can use to achieve the environmental functional target through design parameters to reach the psychological and physical balance for human comfort in the space depending on natural resources in the house design without any artificial resources. All the house elements and spaces are planned to serve the functional target like the courtyard (the center of design), it is designed from the outside to the inside of the house and oriented according to its location and its shape (square or rectangle) and dimensions (L, W, H) are designed to specific ratios, also windows overlooking the courtyard, backyard or the main street is designed to be protruded from the walls to serve the functional parameters, also the geometrical forming emerges in the design of the house elements like Mushrabiya, Shukshieka, Malqaf and arches that proportion is proportioned with the space ratio; from here the effect of geometrical forming in Islamic house design is revealed and reflects the designer creative level in the scope of unchanged environmental functional design parameters; So the study of the form and design of the house and its elements in the Islamic ages enable the architectural to comprehend the mechanism of dealing with the geometrical forming tools to adapt the space to serve the environmental functional parameters.
Keywords: العمارة الإسلامية -- التصميم الداخلي -- التشكيلات الهندسية -- المسكن الإسلامي